Rapid identification method for Russula japonica based on visual and real-time fluorescent loop-mediated isothermal amplification strategies - ZHAO Lanxin; ZHAO Xiaoyan; YI Siliang; TIAN Enjing; FAN Tingting; ZHAO Zhiyong; ZHOU Changyan (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveA method for the rapid detection of Russula japonica was established based on a visual or real-time fluorescent loop-mediated isothermal amplification （LAMP） strategy.MethodsA LAMP primer group targeting the internal transcribed spacer sequence of R. japonica was designed and primer specificity was tested in 23 mushroom species. The sensitivity of the method was assessed by detecting DNA at a series of concentrations ranging from 10 ng/μL to 1 fg/μL.ResultsThe designed primers specifically identified R. japonica without cross-reaction with the other 22 mushroom species. Both developed LAMP methods could detect as low as 2 pg/μL of a DNA template or 1% R. japonica in different mushroom mixtures.ConclusionThe established method is suitable for rapid on-site identification of R. japonica and can be applied to fresh， dried， or cooked mushroom samples， with a detection time of <1 h. This visualization strategy does not require professional equipment and is suitable for the rapid identification of R. japonica.